PENELITIAN TENTANG FORMATIO SPIRITUALITAS DAN KEPRIBADIAN DI RUMAH BINA KARYA ILLAHI MADIUN - Agustinus Wisnu Dewantara (Lembaga Penelitian STKIP Widya Yuwana, 2021)
Rumah Bina Karya Illahi is a house (a kind of dormitory) that accommodates first-level. Rumah Bina organizes a lot of coaching as a basis for students to take further education. Students are active subjects of development, while regulations are only a means of assisting to practice responsibility and life discipline. As development subjects, students must learn to self-regulate, therefore, the foster home also trains students to be responsible for themselves. This research was conducted at the Divine Works Bina House during 2019 s.d. 2020 to measure the four focus areas of coaching (personal maturity, spirituality, study life, and humanities) associated with community rules and events as a means of formation in the foster home so far. The research was conducted by distributing questionnaires to all residents of the Bina House in the period 2019 s.d. 2020. The results showed that most of the students understood the importance of rules in living together, spiritual life, and community life in joint formation. There are quite a number of students who experience formation at Rumah Bina. Rules in living together are needed to maintain orderly living together in the Bina House. Thankfully, the majority of respondents realized the importance of living together, the importance of spiritual events to foster their spirituality, and the need for community events to instill good habits. Orders, spiritual events, and community events are the foundation needed for joint formation.